Assistance for Clients of Correctional Assisted Children : A Study at the Class I Correctional Center in Banda Aceh - Cut Dini Mandasari; Rizanizarli Rizanizarli; Efendi Efendi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Law Number 11 of 2012 emphasizes restorative justice, diversion, and the protection and fulfillment of children’s rights within the juvenile justice system. In addition, Law Number 22 of 2022 highlights the importance of guidance and assistance aimed at supporting the social reintegration of children in conflict with the law. However, the implementation of these legal provisions at the Class I Correctional Center (Bapas) in Banda Aceh has not been fully effective due to several challenges, including the limited number of officers, inadequate initial assistance, and constraints in reporting and inter-institutional coordination. This study aims to analyze the implementation of assistance provided to juvenile correctional clients at Bapas Class I Banda Aceh and identify factors affecting its effectiveness. The research employs an empirical juridical method with descriptive qualitative analysis based on interviews, documentation, and legal literature. The findings reveal that assistance has been provided throughout all judicial stages, including pre-adjudication, adjudication, and post-adjudication processes. These activities involve community research, assistance during diversion and court proceedings, and post-verdict guidance. Nevertheless, implementation remains suboptimal due to internal factors such as limited Community Advisors and heavy workloads, as well as external factors including insufficient family support, limited community acceptance, and weak coordination between institutions. These issues affect the effectiveness of assistance and hinder children’s successful social reintegration.